Effects of Visual Aspects on Consumer Preferences in The Health Supplement Market by Eye-Tracking: Effect of color and shape in health supplement preferences, Eye tracking method - Tahmasebi, Nima; Vatanpour, Hossein; Peiravian, Farzad; Rabinataj, Seyedeh Fahime; Taheri, Saeed (Iranian Journal of Pharmaceutical Sciences, 2022)
Health dietary supplements compared to prescription drugs are different in deciding to consume and the end user is the main decision maker. Packaging plays the most important role in product marketing and branding in the nutritional supplement industry. Packaging shape and color can impact a decision to buy as well as identify what type of item it is and whom it is made for. Packaging factors such as color and shape are important in clinical and marketing aspects. Many types of research on the effect of packaging on psychology or marketing aims have been investigated. This study aimed to evaluate consumers’ preferences for color and shape in oral solid dosage forms (OSDF) by eye-tracking technique. Eye movements are directly correlated to feelings, attention, learning, and reminding of an advertisement or product. This study tried to find consumer preferences by considering eye movements. This study includes two parts: evaluating the independent impact of color and the independent impact of shape on drowning the participants’ attention by tracking the eyes. Thirty participants (15 men and 15 women, aged 20 to 50) with normal and full-color vision participated in the experiment. Images with a neutral (grey) background including 8 colors for each tablet form were made based on previous studies. Images with a neutral (grey) background including 8 shapes for each color were made. Shapes were selected based on the most current shapes used in the pharmaceutical industry. The images were shown to participants and their eye movements were collected by eye tracking device (TobiiT60). The descriptive data analysis indicated that white is the most favored color among the sampling population with a mean vision time of 2252 milliseconds. On the other hand, the pink color was selected as the least favored. For shapes, descriptive analysis of data indicated that the hard gelatin capsules are the most favored dosage form among the sampling population with a mean vision time of 1238 milliseconds. On the other hand, pearl 1 was selected as the least favored compared to other shapes with a mean vision time of 992 milliseconds. Based on the results of this research, the preferable form of general dietary supplement is small and white totally. The results indicated that white color is the most favored color and pink color is the least favored one. In addition, the hard capsule was selected as the most favored dosage form while the pearl was selected as the least favored one. No significant difference between men and women groups was observed. This may be important for pharmaceuticals to produce medicines with the most preferences for both clinical and marketing aspects. Color is the most preferred characteristic with the perception that color is related to the therapeutic indication of supplements. Shape and size can affect preferences regarding the compliance of patients.